2007
DOI: 10.1016/j.jeem.2006.08.002
|View full text |Cite
|
Sign up to set email alerts
|

A revealed preference approach to the measurement of congestion in travel cost models

Abstract: Travel cost models are regularly used to determine the value of recreational sites or particular site characteristics, yet congestion, a key site attribute, is often excluded from such analyses. One reason for this omission is that congestion is determined in equilibrium by the process of individuals sorting across sites and thus presents significant endogeneity problems. This paper illustrates this source of endogeneity, describes how previous research has dealt with it using stated preference techniques, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
88
0
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 141 publications
(97 citation statements)
references
References 19 publications
2
88
0
1
Order By: Relevance
“…One of the strengths of this econometric modeling approach is the ability to decompose the estimation into two stages and use the second stage to disentangle agglomeration or congestion effects from the alternative-specific constant (Timmins and Murdock 2007). We can easily imagine both features existing in fisheries.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…One of the strengths of this econometric modeling approach is the ability to decompose the estimation into two stages and use the second stage to disentangle agglomeration or congestion effects from the alternative-specific constant (Timmins and Murdock 2007). We can easily imagine both features existing in fisheries.…”
Section: Discussionmentioning
confidence: 99%
“…We follow the same estimation routine as the one in Murdock (2006) and Timmins and Murdock (2007). The above contraction mapping problem is solved iteratively, in which the fixed point iteration (4) is nested into the maximum likelihood estimator of (3).…”
Section: The Empirical Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…This may be due to the spatial configuration of such goods and the availability of substitutes [21] or to residential sorting. People's preferences for environmental goods can influence where they choose to live, so that measures of preferences tend to be correlated with measures of environmental quality or with distance to environmental amenities [22]. Recent developments in Geographical Information Systems (GIS) allow researchers to investigate spatial patterns in preferences for environmental goods.…”
Section: Spatially Explicit Discrete Choice Models: Empirical Applicamentioning
confidence: 99%
“…Loomis [10] investigated the impacts of dam removal and river restoration at the Lower Snake River in Washington and concluded that the consumer surplus was $310 million. Timmins and Murdock [11], however, analyzed the random utility models of recreation with congestion and found out that ignoring congestion leads to an underestimate of the Lake Winnebago's value by more than 50%.…”
Section: Introductionmentioning
confidence: 99%